Development of image-based phenotyping for selection characters of rice adaptability on the seedling salinity screening. Issue 3 (July 2021) - Anshori, M F; Farid, M; Nasaruddin; Musa, Y; Iswoyo, H; Sakinah, A I; Arifuddin, M; Laraswati, A A
Abstract: Development of adaptability rice under salinity stress needs effective and selective methods in the screening process. The seedling screening method is a general method used in salinity screening. However, this screening method often uses conventional observation in its screening process. This observation is rated that has a high error level. Therefore, the development of a digital approach through image-based phenotyping expected could minimize the error in the adaptability screening. This study was designed with a nested randomized complete group design, where replications were nested in a stressful environment. The environment in this study was normal (0 mM NaCl) and salinity stress (120 mM NaCl). The genotype used consisted of 8 genotypes which were repeated three times. The number of characters observed was nine image-based phenotyping. The results of this study showed that green percentage, the 3rd leaf length, and total area were the selection characters of image-based phenotyping under seedling salinity screening. Besides that, the used adaptability index in salinity screening became a good approach in considered and distinguished tolerance responses among varieties, especially to Pokkali (tolerant control variety) and IR 29 (sensitive control variety). Based on this study, the application of image-based phenotyping recommended in the screening process of line adaptability under salinity stress.